Adaptive Strategies in Southeast Asia: A Thematic Review on The Evolution of Competition, Cooperation, and Coopetition - Arenal, Arenal; Priyono, Budi; Ardiansyah, Rendy; Pahala, Indra; Handaru , Agung Wahyu (Publikasi Indonesia, 2025)
This study addresses the growing complexity of strategic interactions within organizations in Southeast Asia, focusing on competition, cooperation, and coopetition across Indonesia, Malaysia, Thailand, and Vietnam. Despite extensive research on individual interaction strategies, a comparative and integrative analysis of these dynamics within varying socio-institutional contexts remains limited. The objective is to systematically compare how these strategic interactions manifest in different countries, influenced by their unique economic structures and institutional pressures. Using a thematic literature review, this study analyzes 38 academic articles employing three theoretical frameworks: Resource-Based View (RBV), Institutional Theory, and the Coopetition Strategy Framework. The findings reveal that Indonesia favors coopetition and cooperation based on social and community values, Malaysia emphasizes competitive strategies supported by digital efficiency, Thailand adopts cooperative strategies aligned with public policy, and Vietnam focuses on academic-industry coopetition to enhance innovation. The study highlights that strategic management in the region results from complex interactions between internal organizational resources and external institutional forces. Practically, this research offers insights for managers and policymakers to design adaptive, context-specific strategies that balance competition and collaboration. Future research is encouraged to extend this integrative framework to other ASEAN countries and explore quantitative approaches to better understand coopetition's impact in emerging sectors.